Pengelolaan Stres pada Tenaga Kesehatan selama Pandemi - Shalahuddin, Muhammad Abdurrahman; Mubarok, Musthofa Masyhur (Maternal & Neonatal Health Journal, 2023)
The COVID-19 pandemic has had a variety of impacts, especially on the health side. In addition to the increased workload on health workers, it also brings stress that can cause a variety of physical and mental health problems, including sleep disorders, eating disorders, fatigue, and anxiety disorders. This study aims to identify and analyse stress management strategies in health workers during the COVID-19 pandemic. The technique applied in this study was a qualitative method with a literature study approach, which involved collecting and analysing scientific articles and research reports related to the topic. The study revealed that excessive workload, risk of infection, and persistent emotional distress are the main factors causing stress in healthcare workers. Effective stress management strategies include stress management training, social support, psychological counselling, work-life balance, and access to mental health resources. Proper implementation of mental support programmes can reduce stress and burn out levels, improve mental well-being, and enhance health workers' job performance and satisfaction.